Switch from systemic steroids to budesonide in steroid dependent patients with inactive Crohn's disease. Issue 2 (1st February 2001) - Cortot, A; Colombel, J-F; Rutgeerts, P; Lauritsen, K; Malchow, H; Hämling, J; Winter, T; Van Gossum, A; Persson, T; Pettersson, E
Abstract : BACKGROUND: Steroid dependent patients with Crohn's disease are at high risk of developing glucocorticosteroid induced side effects. AIMS: We evaluated the possibility of switching from systemic steroids to budesonide (Entocort) in prednisolone/prednisone dependent patients with inactive Crohn's disease affecting the ileum and/or ascending colon. PATIENTS: Steroid dependent patients with a Crohn's disease activity index ⩽200 were included. METHODS: In a double blind multicentre trial, 120 patients were randomly assigned to receive budesonide 6 mg once daily or placebo. Prednisolone was tapered to zero during the first 4–10 weeks and budesonide or placebo was given concomitantly and for a further 12 weeks. Relapse was defined as an index >200 and an increase of 60 points from baseline or withdrawal due to disease deterioration. RESULTS: After one and 13 weeks without prednisolone, relapse rates were 17% and 32%, respectively, in the budesonide group, and 41% and 65% in the placebo group (95% confidence intervals for the difference in percentages −41%, −8% and −51%, −16%; p=0.004 and p<0.001, respectively). The number of glucocorticosteroid side effects was reduced by 50% by switching from prednisolone and was similar in the budesonide and placebo groups. Basal plasma cortisol increased in both groups. CONCLUSIONS: The majority of patients with steroid dependent ileocaecal Crohn's disease may be switched to budesonide controlled ileal release capsules 6 mg without relapse, resulting in a sharp decrease in glucocorticosteroid side effects similar to placebo, and with an increase in plasma cortisol levels.